Immunofluorescence staining of paraffin sections: creating DAB staining like virtual digital images using CMYK color conversion - Buchynska, L.; Kashuba, E.; Szekely, L. (Experimental Oncology, 2008)
Crystal violet treatment of formalin fixed paraffin embedded tissue slides greatly reduces the endogenous autofluorescence, and allows immunofluorescence (IF) staining with FITC or Alexa488 conjugated antibodies. Using cold CCD camera to capture the fluorescence images makes this staining method very sensitive. Here we show that combination of IF with the simultaneous recording of crystal violet induced red and Hoechst 33258 induced blue fluorescence permits the localization of the IF signal over a cytoplasmic: nuclear red:blue stain that visualizes the microscopic anatomy of the underlying tissue. To make the visual interpretation of the IF staining easier for microscopists, who are used to DAB staining over weak hematoxilin-eosin background, we created a simple color conversion procedure that turns the captured three-color fluorescence RGB (red, green, blue) images over a black background into four color CMYK (cyan, magenta, yellow, key color (black)) images. Окраска кристаллическим фиолетовым парафиновых срезов, полученных из ткани, фиксированной в формалине, значительно
уменьшает явления аутофлуоресценции и обеспечивает иммунофлуоресцентную (ИФ) окраску антителами, конъюгированными
сFITC или Aleхa-488. Использование CCD-камер для регистрации флуоресцентных изображений делает этот метод очень
чувствительным. Наша цель — разработать метод трансформации RGB (red, green, blue) — флуоресцентных изображений в
CMYC (cyan, magenta, yellow, key color (black) ) изображения. Показано, что комбинация ИФ с одновременной регистрацией
красной и голубой флуоресценции, индуцированной соответственно кристаллическим фиолетовым и Hoechst33258, позволяет
определять ИФ-сигнал как цитоплазматично-ядерное красно-голубое окрашивание, которое визуализирует морфологические
особенности прилегающей ткани. Для упрощения интерпретации ИФ-окраски патологами, привыкшими к окрашиванию
ДАБ на фоне гематоксилин-эозина, нами была создана технология простого цветового перехода, который превращает зарегистрированные
трехцветные RGB-флуоресцентные изображения на черном фоне в четырехцветные CMYC-изображения
на белом фоне, используя программы работы с изображениями.